Oxygen permeability properties of nanocellulose reinforced biopolymer nanocomposites. (2022) - Ilyas, R.A.; Azmi, Ashraf; Nurazzi, N.M.; Atiqah, A.; Atikah, M.S.N.; Ibrahim, Rushdan; Norrrahim, Mohd Nor Faiz; Asyraf, M.R.M.; Sharma, Shubham; Punia, Sneh; Syafri, Edi; Sari, Nasmi Herlina; et al.
Abstract: Dry powder products are highly sensitive to oxygen and water vapour and must have a long shelf life. Currently, they are vacuum-packaged in sachets whose walls are made of a composite film that stops oxygen and water vapour from entering the package. Most of these composites are not biodegradable, a situation that the most agricultural company now wants to change to gain in sustainability. According to National Geography (2019), every year, about 8 million tons of plastic waste escapes into the oceans from coastal nations, with some estimates ranging to at least 400 years to break down. Over the years, there is huge interest in the development and use of biobased packaging materials, however, most of these materials are brittle and have low mechanical properties. Thus, in order to overcome these drawbacks, blended polymers with the reinforcement of nanocellulose are recommended. The aim of this paper is to review packaging films with oxygen barrier properties similar to those of the conventional films but also having biodegradable properties. From the literature, the oxygen permeability coefficient improved with the high strength, modulus, and ductility, as the nanocellulose was reinforcing with biopolymer. This might be due to nanocellulose that contributes to the higher stretchability of the composite biofilms. A fine dispersion of nanocellulose throughout the polymer host promoted several improved properties of the composite biofilms. In addition, nanocellulose had greatly enhanced oxygen and water vapour barrier properties. It would indeed push the usability of biopolymers forward, and certainly, prompt wider application of biodegradable polymers in the fields of environmental protection such as biodegradable food packaging.